The Ecological Fallacy in National Culture Research. Issue 7 (July 2014) - Brewer, Paul; Venaik, Sunil
This article challenges the understanding and use of the Hofstede and GLOBE national culture models in much extant culture-related theory development. Both the Hofstede and GLOBE culture dimensions are derived from individual-level survey data aggregated to, and analysed at, the national level. But their culture scales that are correlated at the national (ecological) level are not correlated in the same manner at the individual or organizational level. To presume they are is a form of 'ecological fallacy' that, despite warnings, has often been overlooked by culture researchers. We analyse five research articles in top journals in organizational behaviour, general management, international business, marketing and accounting and show how the articles commit an ecological fallacy by projecting national-level culture characteristics onto individuals or organizations. The implications of this ecological fallacy include the development of invalid culture-related theory and the persistence of erroneous practitioner stereotyping. We provide the first comprehensive explanation of the origins, effects and implications of the ecological fallacy in national culture research and practice. A way forward for culture-related research is also suggested.